Characterization of Paroxysmal Gluten‐Sensitive Dyskinesia in Border Terriers Using Serological Markers. (9th February 2018) - Lowrie, M.; Garden, O.A.; Hadjivassiliou, M.; Sanders, D.S.; Powell, R.; Garosi, L.
Abstract : Background: Paroxysmal gluten‐sensitive dyskinesia (PGSD) in border terriers (BTs) results from an immunologic response directed against transglutaminase (TG)2 and gliadin. Recent evidence suggests that PGSD is only one aspect of a range of possible manifestations of gluten sensitivity in the breed. Hypothesis/Objectives: Gluten sensitivity in BTs is a heterogeneous disease process with a diverse clinical spectrum; to characterize the phenotype of PGSD using TG2 and gliadin autoantibodies as diagnostic markers. Animals: One hundred twenty‐eight client‐owned BTs with various disorders. Methods: Prospective study. BTs with paroxysmal episodes and a normal interictal examination were phenotyped using footage of a representative episode and assigned to 3 groups: idiopathic epilepsy (IE), paroxysmal dyskinesia (PD), or other. Owners of each dog completed a questionnaire to obtain information regarding clinical signs. Healthy BTs formed a control group. Serum antibodies against TG2 and AGA were measured in all dogs. Results: One hundred twenty‐eight BTs were enrolled; 45 with PD, 28 with IE, 35 with other conditions, and 20 controls. Three overlapping phenotypes were identified; PD, signs suggestive of gastrointestinal disease, and dermatopathy. AGA‐IgG concentrations were increased in PD, compared with IE ( P = 0.012), controls ( P < 0.0001) and other ( P = 0.018) conditions. Anti‐canine TG2‐IgA concentrations were increased in PD, compared with IE ( P < 0.0001), controls ( P < 0.0001) and other ( P = 0.012) conditions. Serological markers are highly specific for PGSD but lack sensitivity. Conclusions: PGSD appears part of a syndrome of gluten intolerance consisting of episodes of transient dyskinesia, signs suggestive of gastrointestinal disease, and dermatological hypersensitivity.